CLINICAL AND MORPHOLOGICAL DESCRIPTION OF DERMIC-FATTY SHREDS OF TEMPORAL AREA - Avetikov, D.S. (World of Medicine and Biology, 2012)
One of serious problems, which arises up at getting up and mobilization of temporal shred is possibility of травматизации frontal-temporal branches of facial nerve, heavy preparation of superficial and deep temporal fascia. Deep temporal fascia consists of superficial and deep layers along the whole length of temporal region, that is not limited only to the place of accumulation of intermediate fatty fabric. Intermediate fatty fabric is important and useful, but not absolute orientir in clinical practice, and the division of fascia can be executed even in default of fatty fabric.
Keywords: temporal fascia; angiosome temporal flap